Faktor-faktor yang mempengaruhi saluran distribusi PT. Tirta Investama Surabaya - Ismail, Muhammad Hijri; Abdilla, Yusrifal Fais; Nirawati, Lia (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
The development of the bottled drinking water (AMDK) business has successfully embedded the values and perspectives of AMDK in Indonesia. In marketing the distribution team has an extensive mineral water distribution network throughout Indonesia. The company has a role to maintain customers by selling distributing products must be done well, distributing products to outlets in a timely and orderly manner, maintaining and maintaining relationships with customers so that they do not switch from our products. The research method used by researchers is quantitative research. The sample in this study is the annual report of PT Tirta Investama for the last three years (2020-2022). The analysis techniques used in this study are descriptions of research data, multiple linear regression tests, normality tests and hypothesis tests. In hypothesis testing there are three tests, namely the t test, F test and determination test. The results of the analysis that have been described answer the objectives and problem formulation of this study. The application of distribution channels at PT Tirta Investama Surabaya is Market coverage can partially affect distribution channels at PT Tirta Investama Surabaya. PT Tirta Investama Surabaya and Goods can partially influence the distribution channels at PT Tirta Investama Surabaya. PT Tirta Investama Surabaya.